2010
DOI: 10.1021/cm100155z
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis and Characterization of Carbon-Supported Pd−Cu Nanoparticle Oxygen Reduction Electrocatalysts

Abstract: The ability to control the size and composition of metal or alloys nanoparticles is important in preparing catalysts. This paper reports a colloidal synthesis methodology for the preparation of monodisperse palladium−copper (Pd−Cu) alloy nanoparticles with an average diameter of 3 nm for the as-prepared particles and 5−10 nm upon removal of the capping agents. Our approach involves the use of metal precursors, capping agents, and reducing agents in controlled ratios for nanoparticle formation in a single organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 61 publications
8
96
1
Order By: Relevance
“…Pd/C / 0.87 A/5 mV s −1 /1600 rpm [195] Pt/C (JM) / 1.05 A/5 mV s −1 /1600 rpm [195] Pd-PPy/C / 0.82 (NHE) A/5 mV s −1 /1600 rpm [196] 40% E-TEK Pt/C / 0.98 (NHE) A/5 mV s −1 /1600 rpm [196] Pd/Vulcan XC-72R 47 at 0.7 V * 0.82 A/5 mV s −1 /1600 rpm [197] 20% E-TEK Pt/C 0.92 A/5 mV s −1 /1600 rpm [197] E-Tek 20% Pd/C 23 at 0.7 V * 0.77 A/5 mV s −1 /1600 rpm [197] PdFe-WC/C / 0.91 A/10 mV s −1 /1600 rpm [198] Pt50Au50/CexC 4.1 at 0.7 V * / A/5 mV s −1 /1600 rpm [180] PdCoMo/CDX975 4.1 at 0.7 V * 0.915 A/5 mV s −1 /1600 rpm [199] Pd/CDX975 1.6 at 0.7 V * 0.84 A/5 mV s −1 /1600 rpm [199] Pd100−xWx / 0.85 A/5 mV s −1 /1600 rpm [200] Pd / 0.7 A/5 mV s −1 /1600 rpm [200] PdPt/C / 0.98 A/5 mV s −1 /1600 rpm [201] Pt rich-core Pd rich-shell 9 at 0.85 V * (catalyst) / A/5 mV s −1 /1600 rpm [202] JM20 Pt/C 5.8 at 0.85 V * (catalyst) / A/5 mV s −1 /1600 rpm [202] Pd/Au 0.34 at 0.8 V * / A/10 mV s PdCu/C 23 at 0.9 V * 0.96 B/10 mV s −1 /1600 rpm [204] Pd-Cu film / 0.86 B/5 mV s −1 /1000 rpm [205] Pd-Co/C 3.6 at 0.7 V * / B/5 mV s −1 /1600 rpm [206] Pt-Pd/C / 0.92 B/5 mV s −1 /1600 rpm [207] Pd/GNS 280 at 0.9 V * 1.06 C/10 mV s −1 /1600 rpm [188] Pt/GNS 110 at 0.9 V * 1.0 C/10 mV s −1 /1600 rpm [188] Pd@MnO2/C 450 at 0.9 V * 1.02 D/10 mV s −1 /2500 rpm [214] Pd black 180 at 0.9 V * 1.07 D/10 mV s −1 /2500 rpm [214] * The potentials were vs. RHE; **solution A: 0. …”
Section: Rate/rotating Speed Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pd/C / 0.87 A/5 mV s −1 /1600 rpm [195] Pt/C (JM) / 1.05 A/5 mV s −1 /1600 rpm [195] Pd-PPy/C / 0.82 (NHE) A/5 mV s −1 /1600 rpm [196] 40% E-TEK Pt/C / 0.98 (NHE) A/5 mV s −1 /1600 rpm [196] Pd/Vulcan XC-72R 47 at 0.7 V * 0.82 A/5 mV s −1 /1600 rpm [197] 20% E-TEK Pt/C 0.92 A/5 mV s −1 /1600 rpm [197] E-Tek 20% Pd/C 23 at 0.7 V * 0.77 A/5 mV s −1 /1600 rpm [197] PdFe-WC/C / 0.91 A/10 mV s −1 /1600 rpm [198] Pt50Au50/CexC 4.1 at 0.7 V * / A/5 mV s −1 /1600 rpm [180] PdCoMo/CDX975 4.1 at 0.7 V * 0.915 A/5 mV s −1 /1600 rpm [199] Pd/CDX975 1.6 at 0.7 V * 0.84 A/5 mV s −1 /1600 rpm [199] Pd100−xWx / 0.85 A/5 mV s −1 /1600 rpm [200] Pd / 0.7 A/5 mV s −1 /1600 rpm [200] PdPt/C / 0.98 A/5 mV s −1 /1600 rpm [201] Pt rich-core Pd rich-shell 9 at 0.85 V * (catalyst) / A/5 mV s −1 /1600 rpm [202] JM20 Pt/C 5.8 at 0.85 V * (catalyst) / A/5 mV s −1 /1600 rpm [202] Pd/Au 0.34 at 0.8 V * / A/10 mV s PdCu/C 23 at 0.9 V * 0.96 B/10 mV s −1 /1600 rpm [204] Pd-Cu film / 0.86 B/5 mV s −1 /1000 rpm [205] Pd-Co/C 3.6 at 0.7 V * / B/5 mV s −1 /1600 rpm [206] Pt-Pd/C / 0.92 B/5 mV s −1 /1600 rpm [207] Pd/GNS 280 at 0.9 V * 1.06 C/10 mV s −1 /1600 rpm [188] Pt/GNS 110 at 0.9 V * 1.0 C/10 mV s −1 /1600 rpm [188] Pd@MnO2/C 450 at 0.9 V * 1.02 D/10 mV s −1 /2500 rpm [214] Pd black 180 at 0.9 V * 1.07 D/10 mV s −1 /2500 rpm [214] * The potentials were vs. RHE; **solution A: 0. …”
Section: Rate/rotating Speed Referencesmentioning
confidence: 99%
“…The enhancement of the activity of the alloy toward ORR was attributed to the change in geometric and electronic structures of Pd caused by the insertion of Cu. Kariuki et al [204] prepared monodispersed PdCu alloy nanoparticles, which showed high ORR activity in acidic electrolyte. Fouda-Onana et al [205] found Pd50Cu50 exhibited the high activity in ORR.…”
Section: Pdcu Alloysmentioning
confidence: 99%
“…Most of these converters consist of electrocatalysts based on noble metal nanoparticles (NPs), such as Pt and Pd. [1][2][3][4][5][6] In this context, the synthesis and characterization of bimetallic or multimetallic NPs have attracted great interest, since they display novel physical and chemical properties, distinct from their monometallic counterparts. [7][8][9][10] Additionally, the properties of nanoalloys can be tuned by changing their size, atomic arrangement and composition.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier reports, there have been some efforts towards synergizing the useful effects of alloying and size reduction by preparing Pd-alloy nanoparticles. [16][17][18][19][20][21] The electronic properties of Pd-Ag and Pd-Cu alloy nanoparticles have been studied as a function of composition using the chemical synthesis routes. 16,17,20,21 Sequential or co-evaporation of the two components using e-beam, thermal heating, sputtering, and laser ablation has been used to prepare Pd-Cu and Pd-Ag alloy thin films and nanoparticulate layers having large variations in composition or phase impurity.…”
Section: Introductionmentioning
confidence: 99%